If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(6n + -4) + 3n = 0 Reorder the terms: -3(-4 + 6n) + 3n = 0 (-4 * -3 + 6n * -3) + 3n = 0 (12 + -18n) + 3n = 0 Combine like terms: -18n + 3n = -15n 12 + -15n = 0 Solving 12 + -15n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -15n = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -15n = 0 + -12 -15n = 0 + -12 Combine like terms: 0 + -12 = -12 -15n = -12 Divide each side by '-15'. n = 0.8 Simplifying n = 0.8
| (x-1.4)=36 | | 36(x-1.4)= | | 20m^2+43m+14= | | 11-45=5(x-3)-4 | | 17(5c-1)-14=83c+17 | | -19n+12=-15n-12 | | 42=-7y | | 11=u-7 | | 2.5h=80 | | 11-12b=3 | | 4u+8=5u+3 | | 2.5=80 | | 4x=3x-7 | | 3y-y=4-18 | | 5t^2-8t=3 | | -3=7y | | -3v=-18 | | 5-8x=55-22x | | 6=v+15 | | -9+14=-2u+7u | | -0.625+m=0.333334 | | -6v-6v=-7-18 | | 7v-1=6v-6 | | 4x+33=14x-77 | | 30X-6=4 | | 5x^3-2=x-x^2 | | 4+3=-2w-3w | | x^2+4x+10=3 | | 7(2x-4)=2x+8 | | 5x+3=4x+4 | | -4+3y=3+1 | | 2x-13=109 |